High proportion of immature oocytes in a cohort reduces fertilization, embryo development, pregnancy and live birth rates following ICSI. Issue 4 (October 2019) - Parrella, Alessandra; Irani, Mohamad; Keating, Derek; Chow, Stephen; Rosenwaks, Zev; Palermo, Gianpiero D.
Abstract: Research question: Ooplasmic maturity has been studied for some time, but remains poorly defined. This study aimed to evaluate metaphase II (MII) oocyte competence in terms of fertilization, embryo development and cycle outcomes, according to the oocyte maturity ratio. Design: Couples treated by intracytoplasmic sperm injection (ICSI) between 1993 and 2017 with female partners ≤35 years old were included. Cycles were divided into four groups according to proportion of MII oocytes at the time of retrieval: optimal (76–100%), adequate (51–75%), partial (26–50%) and minimal (1–25%). Results: A total of 7672 ICSI cycles (optimal: 4838; adequate: 2252; partial: 518; minimal oocyte maturity: 64) were included, in which 95, 667 MII oocytes were injected using ejaculated spermatozoa. The decreasing proportion of MII significantly reduced normal fertilization (two pronuclei) (78.9% to 71.3%; P  < 0.0001) with a corresponding increase in digynic three-pronuclei that rose from 2.6% in the optimal group to 4.7% in the minimal group ( P  = 0.003). Implantation (33% to 17%; P  < 0.0001), clinical pregnancy (63.6% to 37.5%; P  < 0.0001) and live birth rates (49.2% to 26.6%; P  < 0.0001) were affected by the decreasing proportion of MII oocytes. Conclusions: A high proportion of immature sibling oocytes in the retrieved cohort affects the fertilization rate and embryo developmental competence of MII inseminated oocytes, clinical pregnancy and live birth rates, suggesting that, in addition to nuclear maturity, ooplasmic and membrane maturity are required for developmental competence of MII oocytes. These findings may provide guidance toward ovarian stimulation protocols aimed at achieving a greater proportion of MII oocytes, leading to higher fertilization rates and better pregnancy outcomes.